An overview of the recent development of the Ground Source Heat Pump (GSHP) system in China. (July 2023) - Luo, Jin; Zhang, Qi; Liang, Changming; Wang, Haiqi; Ma, Xinning
Abstract: This paper summarizes the development of the Ground Source Heat Pump (GSHP) system in China during the period from 1989 to 2021. A statistical analysis shows the Ground-Coupled Heat Pump (GCHP) system is the major type of GSHP, accounting for 95.09% of the collected 2754 systems. The most likely building types of GSHP are residential and commercial buildings. The development of GSHP can be divided into three stages including the initial stage, the accelerating stage and the steady growing stage. The analysis of distribution density displays the GSHP is majorly located at the Yangtze River Area (YRA) and North China Plain (NCP) area. This matches very well with the potential density of GSHP estimated by considering air pollution, the thermal load of buildings, people density and GDP. Technical measures aiming at the reduction of the costs and the improvement of thermal efficiency of GSHP are the dominated internal factors, policy incentives and energy price are considered the major external factors determining the development of GSHP system.